Evolutionary history of the Pectoral Sparrow Arremon taciturnus: evidence for diversification during the Late Pleistocene. (31st January 2020) - Carneiro de Melo Moura, Carina; Fernandes, Alexandre M.; Aleixo, Alexandre; Farias Pereira de Araújo, Helder; de Freitas Mariano, Erich; Wink, Michael
Abstract : We focus on reconstructing a spatiotemporal scenario of diversification of a widespread South American species, the Pectoral Sparrow Arremon taciturnus (Aves: Passerellidae). This species is widely distributed in both the humid and the dry forests of South America and therefore provides an interesting model for understanding the connection between different biomes of South America. We examined nucleotide sequences of the mitochondrial genes Cytochrome b (cyt‐b) and NADH subunit 2 (ND2) from 107 specimens, and one nuclear marker (intron 7 of the β‐fibrinogen gene) from a subset of samples collected across the distribution ranges of A. t. taciturnus and A. t. nigrirostris. Six major lineages were recovered in the phylogenies that displayed high levels of variance of allele frequencies and corresponded to distinct geographical locations. The estimation of divergence times provided evidence that diversification of the six lineages of the Pectoral Sparrow occurred throughout the Late Pleistocene across major cis ‐Andean biomes and Amazonian interfluves. Our dataset for A. taciturnus provides further evidence that rivers in Amazonia constitute barriers promoting allopatric speciation, with occasional sharing of alleles among lineages, particularly those with adjacent distributions.